2021
DOI: 10.3390/cancers13184518
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Microenvironment-Dependent Transcription Factors AHR and HIF-1α Are Dispensable for Leukemogenesis in the Eµ-TCL1 Mouse Model of Chronic Lymphocytic Leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is the most frequent leukemia in the elderly and is characterized by the accumulation of mature B lymphocytes in peripheral blood and primary lymphoid organs. In order to proliferate, leukemic cells are highly dependent on complex interactions with their microenvironment in proliferative niches. Not only soluble factors and BCR stimulation are important for their survival and proliferation, but also the activation of transcription factors through different signaling pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
2
1
0
Order By: Relevance
“…This genetic experiment is particularly puzzling in view of the significant upregulation of hypoxic gene signatures that was reported in leukemic cells from Eμ-TCL1 mice ( 110 ), thus confirming data obtained by other laboratories of augmented hypoxia signaling in CLL ( 65 67 ). However, HIF1α knock-out did not affect the transcriptional program of Eμ-TCL1 leukemic cells ( 110 ). Therefore, the authors of this paper speculated that compensatory mechanisms may occur that render HIF1α inactivation of no consequence.…”
Section: Hifs and Hypoxia Signaling In Leukemiasupporting
confidence: 85%
See 1 more Smart Citation
“…This genetic experiment is particularly puzzling in view of the significant upregulation of hypoxic gene signatures that was reported in leukemic cells from Eμ-TCL1 mice ( 110 ), thus confirming data obtained by other laboratories of augmented hypoxia signaling in CLL ( 65 67 ). However, HIF1α knock-out did not affect the transcriptional program of Eμ-TCL1 leukemic cells ( 110 ). Therefore, the authors of this paper speculated that compensatory mechanisms may occur that render HIF1α inactivation of no consequence.…”
Section: Hifs and Hypoxia Signaling In Leukemiasupporting
confidence: 85%
“…Similar head-scratching results have been recently published for CLL, where it was shown that knock-out of the HIF1α gene in the Eμ-TCL1 mouse model did not impact CLL progression or increase mice survival, suggesting that HIF1α is not essential for CLL leukemogenesis ( 110 ). This genetic experiment is particularly puzzling in view of the significant upregulation of hypoxic gene signatures that was reported in leukemic cells from Eμ-TCL1 mice ( 110 ), thus confirming data obtained by other laboratories of augmented hypoxia signaling in CLL ( 65 67 ). However, HIF1α knock-out did not affect the transcriptional program of Eμ-TCL1 leukemic cells ( 110 ).…”
Section: Hifs and Hypoxia Signaling In Leukemiasupporting
confidence: 82%
“…Similar results were obtained with the Eμ- TCL1 (TCL1) CLL murine model (GSE175564, ref. 21 ; vs. WT B cells from C57BL/6 mouse; Fig. 1F and G ) as Cd9 , Rab3b , and Rab31 were upregulated (Fig.…”
Section: Resultsmentioning
confidence: 89%